Psychometric validation of the 1-month recall Uterine Fibroid Symptom and Health-Related Quality of Life questionnaire (UFS-QOL) - Karin S. Coyne; Amanda Harrington; Brooke M. Currie; Jun Chen; Patrick Gillard; James B. Spies (SpringerOpen, 2019)
Abstract Background To evaluate the psychometric characteristics of the 1-month recall Uterine Fibroid Symptom and Health-Related Quality of Life questionnaire (UFS-QOL), including the Revised Activities subscale. Methods VENUS I and II were phase III, randomized, double-blind, placebo-controlled trials of ulipristal acetate in women with uterine fibroids (UF) and abnormal uterine bleeding. Women completed the 1-month recall UFS-QOL at baseline and after 12 weeks' treatment. Uterine bleeding was assessed via a daily diary (both studies); the Patient Global Impression of Improvement scale (PGI-I) was completed in VENUS II. Psychometric analyses examined internal consistency reliability and construct validity of the UFS-QOL; confirmatory factor analysis (CFA) compared model fit of the original and Revised Activities subscales. Analyses were conducted separately for VENUS I and II. Results One hundred and fifty-seven patients in VENUS I and 429 in VENUS II were included. Changes in mean Symptom Severity and health-related quality of life (HRQoL) scale scores indicated symptom burden reductions and HRQoL improvements. Cronbach's alpha coefficients were high at baseline and after 12 weeks' treatment (all ≥0.76, meeting the >0.70 threshold), demonstrating strong internal consistency reliability. Correlations between UFS-QOL scores and bleeding diary responses (range: −0.35 to −0.63), and UFS-QOL scores and PGI-I responses (range: −0.48 to −0.70), ranged from moderate to strong after 12 weeks' treatment (all p < 0.0001). Patients with absence of bleeding or controlled bleeding after 12 weeks' treatment scored significantly better (p < 0.001) on each UFS-QOL scale than patients not achieving those end points, supporting construct validity. CFA confirmed model fit for the Revised Activities subscale. Conclusions The 1-month recall UFS-QOL, including the Revised Activities subscale, is a valid, reliable measure to assess UF symptoms and their impact on HRQoL. Trial registration ClinicalTrials.gov, NCT02147197. Registered May 26, 2014; retrospectively registered. ClinicalTrials.gov, NCT02147158. Registered May 26, 2014; retrospectively registered.